The Influence of Usage Frequency and Collaborative Feature Utilization of Google Docs on Communication Effectiveness in Enhancing Collaborative Task Effectiveness Among Faculty of Economic and Business Universitas Negeri Jakarta Students - Putri, Sabrina Resmana; Efendi, Rivana Auliya; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study analyzes the influence of Google Docs usage frequency and collaborative feature utilization on the effectiveness of collaborative tasks among FEB UNJ students, with communication effectiveness as a mediating variable. Using a quantitative survey involving FEB UNJ students selected through purposive sampling and analyzed using PLS-SEM, the results reveal that usage frequency does not significantly influence collaborative task effectiveness (p = 0.089) but has a significant negative effect on communication effectiveness (coefficient −0.270, p = 0.015). The utilization of collaborative features does not have a significant direct impact on task effectiveness (p = 0.725), but it significantly and positively affects communication effectiveness (coefficient 1.123, p = 0.000). Communication effectiveness significantly influences collaborative task effectiveness (coefficient 0.698, p = 0.000) and mediates the relationship between usage frequency (negative, coefficient −0.188, p = 0.041) and feature utilization (positive, coefficient 0.783, p = 0.000) with collaborative task effectiveness. In conclusion, communication effectiveness is a crucial mediator, optimal feature utilization, rather than frequency of use, enhances collaborative task effectiveness through improved communication. Frequent use without proper feature engagement may reduce communication effectiveness. These findings emphasize the importance of digital literacy and the role of educators in guiding students toward meaningful technology use.